ARE YOU WHO YOU SAY YOU ARE? COMPUTER SCIENCE AND THE PROBLEM OF DIVINE SELF‐AUTHENTICATION. Issue 1 (20th November 2021) - McFarlane, Andrew
Abstract: A vital axiom of Reformed theology is that God is who God claims to be, and that he acts to "self‐authenticate" his identity to humans through the internal witness of the Holy Spirit. But how ought theologians to represent and make sense of the multiform nature of divine self‐authentication (DSA)? And can their models account for the various kinds of evidence God utilizes in acts of DSA, or explain why doubt and deception about divine identity persists despite it? Operating at the intersection of theology and computer science, this study examines how modern authentication technologies can deepen theological reflection upon the nature, evidence, and efficacy of DSA. It proposes that computer authentication "trust systems": (1) offer a valuable schematic for representing the variegated structural patterns inherent in DSA; (2) shed critical light on the forms and functions of evidence used in DSA; and (3) provide strategies and practical measures for offsetting the continuing risk of deception about human and divine identity.